Myocardial contusion in athletes - Lateef, F.; Nimbkar, N. V. (International SportMed Journal, 2002)
Myocardial contusion (MC) represents blunt cardiac injury (BCI) in which there is no gross anatomical disruption in the heart (including papillary muscles, chordae tendinae, and valves) or its covering. The cardiac damage results from the compression of the heart between the sternum and spine or from increased intrathoracic pressure from a blow to the chest. Myocardial concussion is distinguished from MC by its lack of myocardial-cell damage, both pathologically and chemically. Athletes have the potential to sustain MC, so adequate protective devices cannot be overemphasized. The exact prevalence of MC among athletes is not known. Diagnosis remains elusive, and no single objective test accurately predicts who will develop morbidity and mortality. Electrocardiography, biochemical cardiac markers, echocardiography, and other imaging techniques have been used in the management of suspected MC. Both early and late complications must be sought. Monitoring in the acute phase and subsequent follow-up must be suggested for all athletes with MC.